The Smart Residential Complex Effect on Personality Formation of Children - Mirpadyab, Seyed Kasra; Khalili Ardali, Atefeh; Bostan, Shakiba; Zamani, Najmeh (Journal of History Culture and Art Research, 2017)
The interaction between human beings and the environment has been a question of all times; however, the Industrial Revolution has begun to change its way. It can be seen that the human beings were a part of their environment in the past, but now with the advancement of knowledge and technology, the man can dominate in their environment. But today, the man’s needs should be well known about the interaction with the natural environment and with respect to the position of the residential complexes in the modern society, these buildings are designed to create the psychological comfort and the formation of the personality. The authors of this paper believe the mentioned event will be happening in the future generation of the buildings. These buildings will be equipped with smart automation system for all their activities. This research conducted by grounded theories about the explanation of the smart residential complexes equipped with the BMS, which can be effective for shaping the managerial character of the children in their future.